The Contribution of Customary Law to Sustainable Development: Social and Environmental Perspectives - Pramidazzura Alifa Rifqi (Journal of Adat Recht, 2026)
This article analyzes the contribution of customary law to sustainable development from social and environmental perspectives within Indonesia’s plural legal system. Although sustainable development is formally embedded in national legal and policy frameworks, its implementation remains predominantly state-centric and technocratic, often marginalizing customary legal systems that have long regulated land use, natural resource management, and social relations. This study identifies three central legal issues: normative ambiguity in positioning customary law within sustainable development governance, a legal vacuum regarding the formal role of customary institutions in environmental regulation, and conflicts of norms between customary law and sectoral development-oriented legislation. Employing a normative juridical method with statute, conceptual, and case approaches, this article examines constitutional provisions, environmental and natural resource laws, and legal doctrines on sustainable development and legal pluralism. The analysis demonstrates that customary law embodies normative principles aligned with sustainability, including ecological balance, communal responsibility, and intergenerational justice. However, these principles remain underutilized due to the absence of explicit legal integration mechanisms. This article argues that the marginalization of customary law weakens both social and environmental dimensions of sustainable development. It proposes a prescriptive framework for integrating customary law into sustainable development governance through statutory clarification, administrative incorporation, and pluralistic judicial interpretation, aimed at enhancing legal certainty, social justice, and environmental protection.